Study of the plastisphere: Biofilm development and presence of faecal indicator bacteria on microplastics from the Río de la Plata estuary - Pazos, Rocío Soledad (2020)
Microplastics (MPs) are considered emerging pollutants and often enter aquatic ecosystems carried by currents and tides until they accumulate on the shorelines. In many cases they may be colonized by diverse microorganisms forming a community called plastisphere, which can even act as a reservoir for pathogenic microorganisms. This study carried out in the Río de la Plata estuary (southern coastal fringe, Argentina) focused on two main objectives, the analysis of the biofilm colonizing MPs under laboratory conditions, and the detection of bacteria indicating faecal contamination (Escherichia coli and Enterococci), in MPs from the intertidal sediment at coastal sites with different land uses, in the freshwater sector of the Río de la Plata estuary. The colonization experiment was carried out in the laboratory with water from the estuary for a period of 35 days (residence time of the water in the freshwater sector of the estuary). The results revealed a remarkable development and diversity of biofilm organisms from the second week of colonization on, covering the surface of the microplastic and thus masking this pollutant. On the other hand, the presence of faecal indicator bacteria in the MPs of the intertidal sediment was confirmed in all the studied sites, being proportionally higher on MPs found in areas influenced by sewage discharges.